2020
DOI: 10.1111/nph.16538
|View full text |Cite
|
Sign up to set email alerts
|

E2 conjugases UBC1 and UBC2 regulate MYB42‐mediated SOS pathway in response to salt stress in Arabidopsis

Abstract: Summary Histone H2B monoubiquitination (H2Bub1) is recognized as a crucial eukaryotic regulatory mechanism that controls a range of cellular processes during both development and adaptation to environmental changes. In Arabidopsis, the E2 conjugated enzymes UBIQUITIN CARRIER PROTEINs (UBCs) ‐1 and ‐2 mediate ubiquitination of H2B. Here, we elucidated the functions of UBC1 and ‐2 in salt‐stress responses and revealed their downstream target genes. Real‐time quantitative PCR assays showed that UBC1 and ‐2 posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…In a positive feedback loop, SOS2 phosphorylates SCaBP8, which enhances the interaction between SOS2 and SCaBP8, resulting in higher plasma membrane Na + /H + exchange activity (Lin et al, 2009). The expression of SOS2 is directly regulated by the MYB domain transcription factor MYB42 under salt stress (Sun et al, 2020) (Figure 2).…”
Section: Sos2 a Central Signaling Transmitter In The Sos Pathway Undmentioning
confidence: 99%
See 1 more Smart Citation
“…In a positive feedback loop, SOS2 phosphorylates SCaBP8, which enhances the interaction between SOS2 and SCaBP8, resulting in higher plasma membrane Na + /H + exchange activity (Lin et al, 2009). The expression of SOS2 is directly regulated by the MYB domain transcription factor MYB42 under salt stress (Sun et al, 2020) (Figure 2).…”
Section: Sos2 a Central Signaling Transmitter In The Sos Pathway Undmentioning
confidence: 99%
“…Interestingly, a recent study identified the glucose sensor HEXOKINASE 1 (MdHXK1) in apple ( Malus domestica Borkh. ), where it phosphorylates MdNHX1 and enhances its activity to confer improved salt tolerance (Sun et al, 2018). As most studies on HXK1 are focused on its roles in glucose sensing, the finding that MdHXK1 participates in salt stress indicates that this protein has broader biological roles in plants.…”
Section: Other Protein Kinases In Salt Stressmentioning
confidence: 99%
“…Salt treatment can induce the degradation of MYB42. This phosphorylation enhances the stability of MYB42 under salt-stress conditions [ 62 ].…”
Section: Mybs Modulate Salt Tolerancementioning
confidence: 99%
“…cDNA samples of GmNAC06 from the OE and VC hairy roots were used to examine the expression level of 14 salt stress-related genes by qRT-PCR (Table S1). The expression level of 2 salt stress-related genes in the OE, VC and WT Arabidopsis were examined by qRT-PCR (Shkolnik et al 2013;Sun et al 2020). The soybean CYP2 gene and Arabidopsis UBQ3 gene were used as a reference for normalization (Ni et al 2013).…”
Section: Stress Treatments and Quantitative Reverse Transcription Pcrmentioning
confidence: 99%